Behavioral Therapy in Post Menopause Patients with Urine Incontinence Problems – Systematic Review - Lenny Nurhandayani; Renny Endang Kafiar; Johan Berwulo (Syntax Corporation Indonesia, 2024)
A journal search was carried out used the keywords